Impact of technological innovation on performance of Vietnamese commercial banks - Tien, Duong Thi Anh (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this paper is to investigate the impact of technological innovation on the cost efficiency of Vietnamese commercial banks from 2009 to 2022. The paper uses the data envelopment analysis (DEA) method combined with the Tobit regression model to examine the impact of technological innovation on the cost efficiency of Vietnamese commercial banks. Using a sample of 35 commercial banks from 2009 to 2022, the findings indicate that technological innovation has a significant positive impact on cost efficiency, suggesting that banks investing in advanced technology tend to improve their operating performance. Furthermore, factors such as profitability, bank size, equity ratio, and economic growth contribute positively to cost efficiency. In contrast, bad debts and inflation are associated with negative impacts. The study concludes that to improve efficiency, commercial banks should continue to invest in technological advancements, strengthen financial capacity, and effectively manage bad debts. These findings provide practical implications for bank managers and policymakers, especially in the context of the ongoing digital transformation in the banking sector.